ChemInform Abstract: Palladium‐Catalyzed ipso‐Borylation of Aryl Sulfides with Diborons. Issue 45 (October 2016) - Bhanuchandra, M.; Baralle, Alexandre; Otsuka, Shinya; Nogi, Keisuke; Yorimitsu, Hideki; Osuka, Atsuhiro
Abstract: Inherently reluctant C—S bonds are transferred into C—B bonds in a catalytic Miyaura‐type reaction.